ASSESSMENT OF NEUTRAL ATMOSPHERIC DELAY PREDICTIONS BASED ON THE TEMPORAL RESOLUTION OF AN ATMOSPHERIC MODEL - Gouveia, Tayná Aparecida Ferreira; Sapucci, Luiz Fernando; Monico, João Francisco Galera; Alves, Daniele Barroca Marra (Boletim de Ciências Geodésicas, 2020)
In Global Navigation Satellite Systems (GNSS), the effects of neutral atmosphere in electromagnetic signal propagation impacts directly on the quality of the final estimated position, leading to errors in the metric order. Using an atmospheric model is a good strategy to minimize these errors, because it becomes possible to obtain a neutral atmospheric delay with the same spatial and temporal resolution, taking into consideration particularities of the atmosphere treated by a numerical model. The regional model of the Center for Weather Forecasting and Climate Studies (CPTEC) used in this paper has a spatial resolution of 15 km and a temporal resolution of 3 hours. Usually, the delay prediction of 3 hours is interpolated in time to GNSS applications and this can influence the quality of the values obtained in each interpolated epoch. Higher temporal resolutions can lead to lower errors in the final position. In this paper, the quality of delay predictions is evaluated for this atmospheric model with resolutions of 6 and 3 hours. The estimated delay, derived from meteorological data in the same location as the geodetic data, is considered as “truth”. The temporal resolution of 3 hours shows better results than using 6 hours, particularly for the hydrostatic component in the initial prediction period, RMSE of 1.25 cm was reduced to 0.2 cm in NEIA station.